Analisis prosedur inventarisasi Barang Milik Daerah (BMD) di Inspektorat Daerah Provinsi Sulawesi Utara - Lumingkewas, Hana Sofie; Saerang , David Paul Elia; Datu , Christian (Riset Akuntansi dan Portofolio Investasi, 2025)
Effective asset inventory procedures are essential to ensure transparency, accountability, and efficiency in the management of government-owned assets. In the context of regional governance, the accurate documentation and control of regional government-owned assets (Barang Milik Daerah/BMD) are vital for supporting good governance, optimizing asset utilization, and minimizing the risk of mismanagement or loss. This study investigates the implementation of inventory procedures for regional assets at the Regional Inspectorate of North Sulawesi Province. Specifically, it aims to (1) analyze the procedures of data collection, recording, and reporting of asset inventory; and (2) evaluate their compliance with the Minister of Home Affairs Regulation Nomor 47 of 2021 concerning the bookkeeping, inventory, and reporting of regional assets. A qualitative descriptive approach was employed, using interviews and documentation analysis as data collection techniques. The findings reveal that the inventory procedures implemented are generally in line with the regulatory provisions. However, several challenges remain, particularly related to data entry, due to limitations in the SIMDA BMD application, which has yet to fully accommodate the updated regulatory framework. These constraints impact the efficiency and accuracy of asset data management. The study highlights the urgency of updating supporting information systems and strengthening technical capacity at the local level. The findings have practical implications for improving asset governance, ensuring regulatory compliance, and enhancing the accountability of regional financial management.